Performing aarti of the goddess - Mumbai Archive Project Team (Jio Institute, 2024)
The idol is installed at an auspicious time, with priests performing the necessary rituals to invoke the presence of the Goddess. After installation, the Goddess is welcomed by aarti (waving the sacred fire in front of the deity).